2003
DOI: 10.1063/1.1566086
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase of NaAlH4: A potential candidate for hydrogen storage?

Abstract: The electronic structure and structural stability of the technologically interesting material NaAlH4 are studied using an ab initio projected augmented plane-wave method for different possible structure modifications. We predict that α-NaAlH4 converts to β-NaAlH4 at 6.43 GPa with a 4 % volume contraction. Both modifications have nonmetallic character with finite energy gaps, the calculated band gap for β-NaAlH4 being almost half of that for the α phase. β-NaAlH4 stores hydrogen more volume efficient than the α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
88
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 19 publications
15
88
0
Order By: Relevance
“…They reported two possible phase transformations: one at ∼3 GPa which was less obvious as a structural transformation, and a second at ∼12 GPa to the orthorhombic structure. Our previous X-ray measurements on commercially available NaAlH 4 showed the phase transformation to ␤-NaAlH 4 phase with orthorhombic structure which is in agreement with the predicted structure by Vajeeston et al [12] followed by amorphisation at ∼13.6 GPa [14].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…They reported two possible phase transformations: one at ∼3 GPa which was less obvious as a structural transformation, and a second at ∼12 GPa to the orthorhombic structure. Our previous X-ray measurements on commercially available NaAlH 4 showed the phase transformation to ␤-NaAlH 4 phase with orthorhombic structure which is in agreement with the predicted structure by Vajeeston et al [12] followed by amorphisation at ∼13.6 GPa [14].…”
Section: Introductionsupporting
confidence: 68%
“…Enhanced desorption kinetics were clearly demonstrated for NaAlH 4 doped with Ti and/or Zr catalyst [9][10][11]. Ab initio calculations by projected augmented plane wave method indicate that NaAlH 4 undergoes a phase transformation from tetragonal structure with space group I4 1 /a, i.e., SrMgH 4 -type structure to the ␤-orthorhombic (Cmc2 1 ) structure at 6.43 GPa with a 45% volume contraction [12]. It was also suggested that the ␤-NaAlH 4 stores more hydrogen volumetrically than the ␣-phase and would, if stabilized at ambient conditions, be an interesting candidate for further studies with regard to hydrogen absorption/desorption efficiency.…”
Section: Introductionmentioning
confidence: 92%
“…A number of results taken from the literature are also shown in these tables for comparison. Vajeeston et al 3 and Ke and Tanaka 4 used the PAW method of VASP with the PBE and PW91 functionals, respectively, to optimize the structure of NaAlH 4 . Opalka and Anton 5 similarly used the PW91 functional with VASP but did not report coordinates for the hydrogen degrees of freedom.…”
Section: Bulk Naalhmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Typically, in these studies some flavor of density functional theory (DFT) 20-22 is used to calculate properties of the bulk solid or of the surface of the solid material. A wide range of DFT methodologies and implementations are currently in regular use for these predictive studies, with little attention being paid to any strengths or weaknesses of particular methods.…”
Section: Introductionmentioning
confidence: 99%
“…(b) There occurs a high-pressure phase transition. Highpressure phases were theoretically predicted for NaAlH 4 (above 64.3 kbar [36]), experimentally found for the lithium analogue LiAlH 4 (tetragonal above 70 kbar and 373-673 K, and orthorhombic above 70 kbar and 773 K [37]). The latter showed a downward shift of the ν 3 [AlH 4 ] − stretching band.…”
Section: Vibrationsmentioning
confidence: 99%